Health-Related Quality of Life in Children and Adolescents with Graves’ Disease in Thammasat University Hospital - Engkakul, Pontipa; Yodvisitsak, Wiraporn (Asian Medical Journal and Alternative Medicine, 2022)
Introduction: Graves’ disease influences physical and mental health as well as health-related quality of life (QoL) in adult patients. However, data of QoL in children and adolescent with Graves’ disease has been limited. Objectives: Thisstudy aimed to measure QoLin children with Graves’disease by means of the PedsQL™ and EQ-5D-Y by using questionnaires in Thai version. Methods: A cross-sectional descriptive study examined 21 Graves’ disease patients with mean age 13.6 ± 3.1 years. All of the participants and their care givers reported the PedsQL™ questionnaires and 20 participants older than 8 years completed the EQ-5D-Y questionnaires. Results: The total mean QoL scores by child- and parent-report PedsQL™ questionnaires were 85.4 ± 17.8 and 82.1 ± 16.3, respectively. Both reported the lowest scores in the emotional functioning domain. The scores by child and parent reports were not different except in the school domain, in which parents reported lower scores. For the EQ-5D-Y questionnaires, 40% of the children reported some problems in the domain of having pain or discomfort and 40% reported some problems in the domain of feeling worried, sad or unhappy. Mean (SD) EQ-5D visual analogue scale value was 86.5 ± 12.0. Conclusions: Children and adolescents with Graves’ disease reported their lowest QoL scores in the domain of emotional functioning, followed by the physical functioning domains. However, the total QoL score was not lower than total QoL scores in previous studies of general healthy populations.